Pengaruh Desain Kemasan, Word of Mouth, Dan Harga Terhadap Keputusan Pembelian Cimory Yogurt Squeeze (Studi Kasus : Pada Mahasiswa Universitas Samudra) - Julianti, Safitri; Indah, Dewi Rosa; Safrizal, Safrizal (Jurnal Manajemen Akuntansi (JUMSI), 2022)
The purpose of this study was to determine the effect of packaging design, word of mouth, and price on the purchasing decision of Cimory Yogurt Squeeze. The sample used in this study amounted to 96 respondents. The data analysis method used multiple linear regression analysis, t test, F test, and coefficient of determination test. From multiple linear regression analysis, the regression equation Y = 4.160 + 0.273X1 + 0.320X2 + 0.155X3. From the t-test, it is known that the packaging design, word of mouth and price partially have a significant effect on purchasing decisions for Cimory Yogurt Squeeze at Samudra University students. From the F test, it is known that the packaging design, word of mouth and price1 simultaneously1 have a significant effect on the purchasing decision of Cimory Yogurt Squeeze at Samudra University students1